Analisis Pemanfaatan Madu Hutan (Apis dorsata) Berbasis Konservasi di Taman Nasional Ujung Kulon - Dani Hermawan; Mufti Sudibyo; Sodikin Sodikin (Universitas Nahdlatul Ulama Blitar, 2026)
This study aims to formulate an optimization strategy for sustainable wild honey (Apis dorsata) utilization within the Ujung Kulon National Park, specifically on Panaitan Island. Adopting a mixed-methods approach, the research integrates spatial ecological analysis, socio-economic mapping of the Wild Honey Farmers Group (KPMH), and strategic evaluation using SWOT and Analytical Hierarchy Process (AHP) methods. Ecological analysis reveals that honeybees predominantly select Kiara, Tongtolok, and Kepuh as host trees, with an average nest height of 18.2 meters. Although the KPMH has implemented sustainable harvesting practices, business sustainability remains hindered by limited working capital, low post-harvest product quality, and the fluctuating risk of forest fires. The SWOT analysis positions the strategy in Quadrant I (Aggressive), supported by internal and external scores of +0.67 and +2.23, respectively. Meanwhile, the AHP results prioritize post-harvest quality improvement and collective capital access (score 0.391). This research concludes that strengthening economic sustainability is an absolute prerequisite for ensuring conservation compliance and habitat preservation through the transfer of dehumidifier technology, business legalization, and the establishment of an integrated aggregator cooperative.